Review-Tanaman Porang (Amorphophallus muelleri Blume) dan Potensinya untuk Diversifikasi Pangan - Emilda Emilda (Jurnal Teknologi dan Mutu Pangan, 2024)
The threat of a food crisis must be addressed immediately, especially ensuring the fullfillment of staple foods such as rice. The food diversification program should be used as an anticipatory strategy. Because Indonesia has a diversity of local food from tubers and cereals as a substitute for rice. The porang plant is one of the local foods that has the potential to be developed. The aim of makingthis article is to analyze the potential and opportunities for developing porang to encourage of food diversification programs. The method used is a literature review with a descriptive approach using secondary literature. The results shows that porang has been widely cultivated. This plant has great potential as a substitute for rice because of its high carbohydrate content. Apart from that, porang is rich in glucomannan which is very good for health. Glucomannan is a water-soluble polysaccharide fiber which is beneficial for the body such as maintaining body weight, controlling cholesterol, reducing the risk of cancer, etc. Porang is widely used by the food industry as an emulsifier and thickener. However, the provision of quality seeds in sufficient quantities and the availability of glucomannan purification technology that is easily accessible to the public are obstacles in developing porang. To overcome this, an integrated, comprehensive and harmonious policy is needed starting from the production aspect, price guarantees and providing technology for processing porang tubers. On the other hand, this policy must also be supported by the community by starting to build the habit of consuming porang in households